The Effect of Digital Marketing and CRM on Repurchase Intention with Customer Experience Mediation at Consina Store Pontianak on Shopee - Fauzan, Ahmad Hilmi; Fauzan, Rizky; Fitriana, Ana; Listiana, Erna; Ahmadi (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
The rapid development of digital technology has significantly transformed consumer behavior and business practices across various countries, including Indonesia. This study examines the relationship between digital marketing strategies, customer relationship management (CRM), and customer experience in shaping repurchase intention on the Shopee platform, with a specific focus on Consina Store Pontianak. A quantitative approach was employed using a survey design and purposive sampling of 163 respondents who have purchased or plan to purchase products from Consina Store Pontianak via Shopee. Data were collected through Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The model assessment included indicator validity, reliability, discriminant validity, and structural analysis to test the relationships between variables using path coefficients, t-statistics, and p-values. The results reveal that digital marketing does not have a direct significant effect on repurchase intention; however, customer experience plays a crucial mediating role between digital marketing, CRM, and repurchase intention. CRM has a strong positive influence on both customer experience and repurchase intention. These findings highlight the importance of personalized customer interactions and effective relationship management in driving purchasing decisions on e-commerce platforms like Shopee. By integrating digital marketing, CRM, and customer experience, this study provides both theoretical and practical contributions for e-commerce business practitioners. The synergy among these three aspects is key to enhancing repurchase intention and maintaining competitive advantage in Indonesia’s digital era